Integration of 4C Skills in Physical Education Learning Strategy Module - Karo Karo, Alan Alfiansyah Putra; Sari, Liliana Puspa; Hendrawan, Dicky (Universitas Pendidikan Ganesha, 2025)
Students often experience difficulties in understanding lecture material when creative and contextual learning resources are not available. Low interest and motivation to learn are additional challenges in the lecture process. This study aims to develop and evaluate the feasibility of a module of Physical Education learning strategies integrated with 21st century skills, with a focus on 4C abilities (critical thinking, communication, collaboration, and creativity). This study used the research and development (R&D) method by involving material experts, media experts, user lecturers, and students as test subjects. Data collection was done through observation and questionnaire, while data analysis used quantitative and qualitative approaches. The results showed that the module feasibility assessment by material experts reached 72% (feasible), media experts 74% (feasible), user lecturers 78% (feasible), and student users 79% (feasible). These findings indicate that the developed learning module is considered feasible for use in the lecture process and has the potential to improve student learning outcomes. This module also contributes to improving students' critical thinking skills, communication, collaboration, and creativity in the context of Physical Education learning. Therefore, the application of this 4C-based module is recommended as an alternative strategy in improving the quality of learning in higher education, especially in the Physical Education learning strategy course.